Calendar of Thomas Jefferson - Jefferson, Thomas, 1743-1826.
Annotated calendar.
Microfilm of originals in the library of the U.S. Dept. of State, Washington, D.C.
U.S. Dept. of State Library
U.S. president, vice president, and secretary of state; diplomat, architect, inventor, planter, and philosopher.
Keywords: Cabinet officers; Diplomats; Plantation owners; Presidents -- United States; Vice-Presidents -- United States